The effect of sitting position on double poling cycle characteristics, trunk control and physiology in sit-skier : a case study - Sampolahti, Ville (2020)
Introduction. Paralympic sit-skiing was introduced in Paralympics 1988. Since that, it has been involved to International Paralympic Committee’s competitions (IPC). The athletes have been divided into five different classes based on the level on impairment and loss of trunk control. The classification is three-stepped process, where the level of the impairment and trunk control of the athlete is evaluated. In cross-country sit-skiing, the athletes perform by using double poling technique Methods. In this case study, the subject was a Finnish 28-years old sit-skier, who is classified to class LW11. The aim was to test the possible benefits of “kneeing” position with the impaired subject who has performed in “knee-high” position. The measurements took four days. During that time, the subject performed in both positions in maximal power output and submaximal tests in ski ergometer as well as in maximal oxygen uptake test and two anaerobic tests on treadmill. EMG, joint kinematics, cycle characteristics and blood lactate were measured from each test. The respiratory variables were measured from submaximal loads in ski ergometer and maximal tests on treadmill. Pole forces were measured from maximal tests on treadmill. Results. The main finding of this case study was that in the “kneeing” position, the subject recorded longer time of exhaustion in maximal oxygen uptake test, higher maximal speed on treadmill, longer time of exhaustion in anaerobic uphill test and higher maximal power (W) in ski ergometer. There was no difference in VO2peak values, but B-Lapeak was clearly higher in “kneeing” position in each test on treadmill. The trunk range of motion was limited in “kneeing” position compared to “knee-high” position. Longer cycle time and lower cycle rate were suggested to be the key patterns of double poling and connected with more economical double poling performance in the maximal test and in both anaerobic tests. Conclusion. The present results show that even for the athlete with limited trunk control, the “kneeing “position can affect positively to sit-skiing performance. How this new sitting position will work in the future and will the athlete due to the increased workload of the erector spinae muscles be able to continue with the new position remains to be seen. Nevertheless, based on this case study, we have now a protocol to test sit-skiing athletes, the performance of them and the differences between the classes and the positions on a treadmill.